Bahasa Mandarin Sebagai Medium Dakwah Kajian Terhadap Malaysian Chinese Muslim Association (MACMA) - Safinah Ismail; Nur Aisyah Abu Hassan; Aemy Elyani Mat Zain; Nur Damia Husna Nor Sad; ,Siti Zahidah Mu’al (USIM Press, 2024)
Vol. 6 No. 3 (2021): Special Issue